Jezični utjecaj velikih gradova - Kapović, Mate (2004)
The aim of this article is to show the linguistic influence of the four biggest cities in Croatia – Zagreb, Split, Rijeka and Osijek on their surrounding region. The article shows that the speakers of the organic idioms considerably farther from the standard when trying to speak the standard do not really adjust their speech to the standard but, mainly on the prosodic and somewhat less on the phonemic level, tend to adapt their manner of speaking to the speech of the town center of their region and while thinking they are speaking &laquo ; ; more standardly&raquo ; ; they are really getting even farther from the standard.
HRV